Use of Statin and Target Low-density lipoprotein cholesterol attainment among post-ST elevation myocardial infarction patients in Shahid Gangalal National Heart Centre, Kathmandu, Nepal - Adhikari, Chandra Mani; Prajapati, Dipanker; Timalsena, Birat; Bogati, Amrit; Khan, Barkadin; Safi, Sajjad; Adhikari, Jagat; Ghimire, Vijay (Journal of Nepal Health Research Council, 2024)
Background: and objective: Lipid-lowering is an important intervention to reduce cardiovascular morbidity and mortality in the secondary prevention of STEMI. There is no study to analyze the use of statin and LDL-C treatment target attainment among STEMI patients in Nepal. This study aims to assess the use of statin and LDL-C treatment target attainment among STEMI patients.Methods: It was a prospective observational single-center study conducted at the Shahid Gangalal National Heart Centre, Kathmandu, Nepal outpatient department. An outpatient department-based survey was conducted among STEMI patients who have lipid profile levels at the time of admission for STEMI and after 4-13 weeks of the index event. Lipid profile levels, diagnosis, and risk factors were collected during the outpatient follow-up.Results: Our study included 280 post-STEMI patients; the mean age was 57.5±11.7 years with the majority being male. The mean duration of follow-up was 6.7 ± 0.1 weeks. Rosuvastatin was the preferred statin with 82.1%. The most common dose of statin used was Rosuvastatin 20mg (70%), followed by Atorvastatin 40mg (12.5%). LDL-C levels of <1.4mmol/l were achieved in 44.6% of cases and LDL levels of <1.8mmol/l in 71.8% of cases. In 36.8% of the study population, there was a greater than 50% decline in LDL-C levels. Diabetic patients (55.1% and 83.1%) only have the significant achievement of LDL goal of both <1.4mmol/l and <1.8mmol/l respectively, when compared to those without diabetes (44.9% and 16.9%).Conclusions: Most of the post-STEMI patients were treated with high doses of statins and achieved the target LDL-C levels.Keywords: Atorvastatin; Low-density lipoprotein cholesterol; Rosuvastatin; STEMI.